Diet dependent olfactory response and predation rate of Neoseiulus californicus (Acari: Phytoseiidae) in the presence of Frankliniella occidentalis and Tetranychus urticae - Kimia Emami; Azadeh Zahedi Golpayegani; Alireza Saboori (Persian Journal of Acarology)
Responses of female predatory mite, Neoseiulus californicus (McGregor) (Acari: Phytoseiidae) with different diet experiences were examined in a Y-tube olfactometer. The odor sources were clean air vs. clean bean leaves, clean air vs. Tetranychus urticae (Koch) (Acari: Tetranychidae) infested bean leaves, and T. urticae infested bean leaves vs. clean bean leaves. Female predatory mites that fed on T. urticae as their previous diet for three generations, preferred clean leaves, spider mite infested leaves and again spider mite infested leaves over the alternative odor sources. When N. californicus was fed on T. urticae plus pollen, a significant movement was recorded towards clean leaves rather than clean air, but no significant preference was observed in two other olfactory experiments. Feeding on pollen alone, thrips first instar alone and thrips first instar plus pollen, the predators did not make a significant preference towards the arms in any of the olfactory experiments. Comparing the mean foraging time and predation rate of N. californicus when their prey (T. urticae) were experienced in a direct contact with Frankliniella occidentalis with predators whose prey had previousely received signals due to thrips (F. occidentalis) presence, we recorded a significantly higher foraging time and consumed prey in the patches where thrips were removed. According to our results, N. californicus is capable of detecting its prey and patches with heterospecific (F. occidentalis) and conspecific predators through its diet-based-understanding of chemical cues. Explanations for the olfactory response and foraging behavior of N. californicus are discussed.